Simulation analysis of reflective performance of marking glass beads. Issue 4 (June 2021) - Leng, Zhengwei; Wang, Luwan; He, Huayang; Wang, Rui
Abstract: Road traffic markings are made of glass beads embedded in paint. To analyze the effects of glass-bead radius, embedment depth, correlated color temperature of light sources, and incident angle on the reflective performance of glass beads, a numerical model is established using the geometric optics method, effective light conditions are analyzed, calculation methods for optical power devised, and non-standard planes of incident light calculated. Calculations were also carried out. Results show that the retroreflective properties of glass beads are positively correlated with the correlated color temperature of the light source and radius of the beads. The glass-bead radii, embedment depths, and incident angles have little effect on their reflective performance. Moreover, the correlated color temperature of the light source is an important factor affecting the accuracy of measuring glass-bead reflective performance. When using retro reflectometers, standard retro reflectance-measuring devices for retro reflectance measurement, and other equipment to evaluate the reflective performance of road traffic markings, the correlated color temperature of the light source of the equipment should be as close as possible to 2856 K.